Gabriela Mistral's «Sonnets to Ruth»: The Consolation of Passion - Howard M. Fraser (Studies in 20th & 21st Century Literature, 1978)
As for many poets, the sonnet form presented the opportunity to Gabriela Mistral to perfect her poetic technique. This study examines in detail the Nobel Laureate's trio of sonnets commemorating the biblical matriarch Ruth. Mistral's treatment of the themes of alienation, self- sacrifice, and the search for human dignity features the contrasts of suffering and consolation which are present in the biblical narrative. But, alongside the thematic purposes which the pleasure/pain duality serves, Mistral exploits this opposition for technical and structural reasons. She uses the feelings of love and pain as an organizational device in her treatment of time, characters and diction. The discipline with which she handled traditional metres, in this case the sonnet, reveals that Mistral was a capable and mature poet at an early age.
Keywords: Gabriela Mistral; Sonnets to Ruth; poetry; alienation; self-sacrifice; human dignity